To simplify -6 (1/4 x - 2/3 x + 5/6 x), we can first combine the x terms with the same denominator:
-6 (1/4 x - 2/3 x + 5/6 x)
= -6 (3/12 x - 8/12 x + 10/12 x)
= -6 (5/12 x)
Now, we can multiply the whole number and the fraction:
-6 (5/12 x)
= -30/12 x
Therefore, the simplified form is -30/12 x.
Simplify -6 (1/4 x - 2/3 x+ 5/6 x)
3 answers
simplify -30/12 x
To simplify -30/12 x, we can reduce the fraction:
-30/12 x
= (-15/6) x
= (-5/2) x
Therefore, the simplified form is (-5/2) x.
-30/12 x
= (-15/6) x
= (-5/2) x
Therefore, the simplified form is (-5/2) x.